Acceptance and Use of E-Procurement in Ogan Ilir Regency with Behavioral Intention as a Mediating Variable - Deta Helisa Nova; Kgs. M. Sobri; Abdul Nadjib (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study examines the factors influencing the implementation of e-procurement in the Ogan Ilir Regency, considering the role of behavioral intention as a mediating variable and using the UTAUT framework as the analytical foundation. With a quantitative approach and survey method involving 145 respondents from UKPBJ in Ogan Ilir Regency, with data analyzed using the SEM-PLS technique. The findings reveal that performance expectancy, effort expectancy, and social influence significantly affect behavioral intention while facilitating conditions impact e-procurement usage directly. The findings also show that behavioral intention significantly affects e-procurement usage, highlighting the crucial role of user intention in technology adoption. Moreover, behavioral intention effectively mediates the impact of performance expectancy and social influence on e-procurement usage. In contrast, effort expectancy does not show a significant effect through this mediating variable. These results support the UTAUT theory, which emphasizes the importance of behavioral intention in technology adoption. From a practical perspective, e-procurement managers need to enhance perceptions of benefits, ease of use, and social support, and provide adequate facilities to boost interest and usage in e-procurement. This study offers valuable insights for improving transparency, efficiency, and accountability in procuring goods and services in Ogan Ilir Regency.